New marine low trophic resources as food: nutritional and food safety aspects - Elvevoll, Edel Oddny; Eilertsen, Karl-Erik; Aschan, Michaela; Bandarra, Narcisa Maria (Frontiers in Aquaculture, 2023)
Food agencies recommend increasing the consumption of aquatic food to promote healthy living and sustainability, and, particularly, to prevent Western lifestyle-related diseases and secure sustainable food systems. This requires growth in global seafood production, and the utilization of low trophic species (LTS) is suggested. LTS are already considered nutritious and important in Asian and Pacific diets. As the use of LTS is expanding in Western diets, producers and consumers need information on the food safety practices associated with them and their nutritional content. LTS are mainly immobile or slow-moving extractive species or organisms that feed on such, and their nutrient and contaminant content varies by species and location. Species-specific knowledge on nutritional contents and safe consumption limits is often missing, making the monitoring and analysis of contaminants, nutrients, and consumption data crucial to guiding the utilization and consumption of LTS. Using global and regional standards regarding nutrients, food hazards, and labeling, this review highlights the appropriate guidelines and regulations for guiding the utilization of selected novel species and also identifies knowledge gaps.